2022
DOI: 10.1029/2021wr030799
|View full text |Cite
|
Sign up to set email alerts
|

Drought Cycle Analysis to Evaluate the Influence of a Dense Network of Small Reservoirs on Drought Evolution

Abstract: The construction of reservoirs without a systematic and holistic analysis of the watershed can lead to a concentration of water in certain parts of the basin, and scarcity elsewhere (Di Baldassarre et al., 2018). In this way, reservoirs can intensify or induce drought events, defined as periods of exceptional lack of water that negatively impact human activities or environmental demands (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…In dry regions, the water stored in reservoirs has a fundamental importance to supply the population's water demand during the dry seasons and droughts, as well as the use of water for industrial processes and food production by irrigation [2]. The increase in the population and the consequent growth in water demand, combined with climate and land use changes, have put pressure on water resources and increased the risk of severe hydrological droughts over the years in these dry regions [3]. The combination of strategic reservoirs with many small reservoirs in dryland catchments generates a Highdensity Reservoirs Network (HdRN) that should improve water security, but it can modify streamflows during dry and wet periods.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In dry regions, the water stored in reservoirs has a fundamental importance to supply the population's water demand during the dry seasons and droughts, as well as the use of water for industrial processes and food production by irrigation [2]. The increase in the population and the consequent growth in water demand, combined with climate and land use changes, have put pressure on water resources and increased the risk of severe hydrological droughts over the years in these dry regions [3]. The combination of strategic reservoirs with many small reservoirs in dryland catchments generates a Highdensity Reservoirs Network (HdRN) that should improve water security, but it can modify streamflows during dry and wet periods.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the construction of small and medium-sized reservoirs has intensified in recent decades. These small reservoirs (below 1 million m 3 ) are often built by the population itself or by farmers as they are essential for the availability of water in these rural communities. In addition to the importance of reducing inequality in the water distribution for water-scarcity regions, these small reservoirs have low costs [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, holding back water upstream exacerbated hydrological drought downstream (van Langen et al., 2021) and the perceived increased water security that reservoir construction provided may have led to further unsustainable water use. The impact of these small reservoirs would likely be unknown in any physical examination due to uncertainty over their number and capacity; only further diagnostic testing , such as through remote sensing analysis and numerical modeling, can show that their presence can extend hydrological drought by up to 80% (Ribeiro Neto et al., 2021). What's more, de Araújo and Bronstert (2016) demonstrated that the small informal reservoirs are an insufficient treatment for smallholders as they cannot buffer long‐term droughts.…”
Section: Drought Case Studiesmentioning
confidence: 99%